Preserving the Normal Healthy Testis: Role of Beta-carotene - Abdulla Ahmad (University of Mosul, 2022)
Background: Many drugs can have significant deleterious side effects on the different organs of the body which can change normal physiology to different pathologies. Recent research have been focusing on valuable methods to preserve the normal healthy testis from the medications’ adverse effects. The study aims to investigate the role of beta-carotene in the protection against potential amikacin’s testicular toxicity. Materials and methods: Male rats were involved in the study. Rats have divided into four groups: the first group was control, the second group has been given amikacin as an inducer of testicular toxicity; the third group has been given both amikacin and beta-carotene, and the fourth group has been given beta-carotene as prophylaxis before induction of the toxicity. The histological architecture of the testis was investigated for all the rats. Results: Amikacin caused a significant deleterious effect which included degeneration and necrosis of cells of seminiferous tubules as well as atrophy and congestion of blood vessels. Co-administration of both beta-carotene and amikacin resulted in a partial improvement in the testicular tissue while using beta-carotene as prophylaxis succeeded in protecting and preserving the normal histological features of the testis completely. Conclusion: The study concluded that beta-carotene can preserve the normal physiological testis and protect it against the amikacin’s deleterious effect on the testis.